(D+10) MELD as a novel predictor of patient and graft survival after adult to adult living donor liver transplantation. Issue 5 (4th April 2017) - Soin, Arvinder Singh; Goja, Sanjay; Yadav, Sanjay Kumar; Tamang, Tseten Yonjen; Rastogi, Amit; Bhangui, Prashant; Thiagrajan, Srinivasan; Raut, Vikram; Babu, Raghvendra Y.; Saigal, Sanjiv; Saraf, Neeraj; Choudhary, Narendra Singh; et al.
Abstract: We modified the previously described D‐MELD score in deceased donor liver transplant, to (D+10)MELD to account for living donors being about 10 years younger than deceased donors, and tested it on living donor liver transplantation (LDLT) recipients. Five hundred consecutive LDLT, between July 2010 and December 2012, were retrospectively analyzed to see the effect of (D+10)MELD on patient and graft survival. Donor age alone did not influence survival. Recipients were divided into six classes based on the (D+10)MELD score: Class 1 (0‐399), Class 2 (400‐799), Class 3 (800‐1199), Class 4 (1200‐1599), Class 5 (1600‐1999), and Class 6 (>2000). The 1 year patient survival (97.1, 88.8, 87.6, 76.9, and 75% across Class 1‐5, P =.03) and graft survival (97.1, 87.9, 82.3, 76.9, and 75%; P =.04) was significantly different among the classes. The study population was divided into two groups at (D+10)MELD cut off at 860. Group 1 had a significantly better 1 year patient (90.4% vs 83.4%; P =.02) and graft survival (88.6% vs 80.2%; P =.01). While donor age alone does not predict recipient outcome, (D+10)MELD score is a strong predictor of recipient and graft survival, and may help in better recipient/donor selection and matching in LDLT.